Applying A Swot Analysis Approach To A Sharia Marketing Perspective At Alunicorn Shops In Bandung - Rianda Hanis; Muhammad Yusuf (Universitas Kristen Indonesia Toraja, 2022)
This research is motivated by advances in internet technology which are currently growing rapidly in society. Digital marketing strategies are an alternative way for business people to reach consumers very broadly and quickly in promoting their products via the internet and to increase sales volume. The purpose of this study is to determine the application of Fihadaessie's digital marketing strategy in developing business by promoting products that can increase sales turnover as measured using the SWOT matrix and to review the digital marketing strategy whether it is in accordance with sharia marketing principles. This research was conducted using a descriptive qualitative approach using the IFAS Matrix, EFAS Matrix, and SWOT Matrix to measure strengths, weaknesses, opportunities and threats. Source of data obtained from primary data and secondary data. Data collection techniques through observation, interviews and documentation. The results of this study indicate that the implementation of digital marketing strategies has been successfully implemented through social media WhatsApp, Instragram, Shopee and Tiktok so that there has been an increase in turnover and the implementation of digital marketing strategies is in accordance with sharia marketing principles. From the results of the IFAS matrix, it is strong in identifying internal factors, the EFAS matrix is ​​good at responding to existing opportunities and avoiding threats that come from competitors. The results of this study indicate that the implementation of digital marketing strategies has been successfully implemented through social media WhatsApp, Instragram, Shopee and Tiktok so that there has been an increase in turnover and the implementation of digital marketing strategies is in accordance with sharia marketing principles. From the results of the IFAS matrix, it is strong in identifying internal factors, the EFAS matrix is ​​good at responding to existing opportunities and avoiding threats that come from competitors. The results of this study indicate that the implementation of digital marketing strategies has been successfully implemented through social media WhatsApp, Instragram, Shopee and Tiktok so that there has been an increase in turnover and the implementation of digital marketing strategies is in accordance with sharia marketing principles. From the results of the IFAS matrix, it is strong in identifying internal factors, the EFAS matrix is ​​good at responding to existing opportunities and avoiding threats that come from competitors.